Studies of E-Learning in Practice - Rechberger, Manfred (International Journal of Advanced Corporate Learning (iJAC), 2017)
Computer assisted and computer based applications become more and more important in everyday lives. Their implementation in the field of music education seems to become a long-term project. Whereas years ago we were sure about the fact, that the quality of e-learning at our University of Music and Performing Arts depends on the implementation of audio-visual media at our e-learning platform, nowadays the text based tasks and written journals have won the race at least in the statistic of usage. Many modules containing multimedia based content promote creative processes and different learning situations. Advantages of e-learning include flexibility and convenience for learners, especially if they have more variety in learning experiences by using multimedia applications. This paper deals with the change of our user behaviors in the last years, discussion forums, blogs, wikis and collaborative online activities and focuses on tools for musicians, composers and music scientists based on the actual status of the discussions in media pedagogies. A scientific project including surveys about the advantages and disadvantages of digital teaching repositories describes common used online music tools.